(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Genetic diversity in 31 traditional Bangladeshi Aus rice genotypes were studied under transplanted condition through Mahalanobis D2 statistic for grain yield and yield contributing characters. The genotypes were grouped into five clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster II contained the highest number of genotypes (08) and the cluster I and III contained the lowest (05). The highest intra-cluster distance was noticed for the cluster II and the lowest for cluster IV. The highest inter-cluster distance was observed between cluster II and V followed by cluster III and V, cluster I and V and the lowest between cluster I and III. Regarding inter-cluster distance, the genotypes of cluster V showed high genetic distance from all other clusters. The genotypes from cluster V could be hybridized with the genotypes of other characters of other clusters for producing transgressive segregants. The highest cluster means for yield, effective tiller number and grain length, were obtained from cluster I; whereas the lowest mean value for yield, culm length, plant height and grain breadth were found in cluster II. Therefore, genotypes under cluster I, cluster II and cluster V might be selected for future breeding program as parents for crossing to produce new recombinants with desired traits. Bangladesh J. Agril. Res. 43(2): 253-266, June 2018